Doing Justice to the Future: A global index of intergenerational solidarity derived from national statistics - Jamie McQuilkin (Intergenerational Justice Review)
This paper proposes an index of national levels of “intergenerational solidarity”, defined as “investments or sacrifices that are intended to increase or sustain the wellbeing of future generations”. This is measured by examining changes to the value and stability of various capital flows and stocks. Nine indicators are drawn from national-level statistics: forest degradation rate, share of low-carbon energy consumption, and carbon footprint in the environmental dimension; adjusted net savings, current account balance, and wealth in equality in the economic dimension; and primary pupil-teacher ratio, fertility rate, and GDP-adjusted child mortality in the social dimension. This returns a comparative index score of intergenerational solidarity for 120 countries covering 92% of the world’s population. Throughout, the state of the current research on intergenerational transfers and on the individual metrics used is discussed, and suggestions are made for further improvements and work in measuring intergenerational solidarity. As it stands, the index provides the widest coverage of indicators and nations aimed at measuring any similar concept. As such, it is particularly useful for those who wish to investigate the causes of intergenerational solidarity through cross-cultural comparisons.